Her Body Remembers: Jerusalem, Memory and Forgetfulness in Contemporary Israeli Cinema - Zanger, Anat (MiKAN, 2017)
In this article Zanger seeks to trace Jerusalem cinematic space as a dialectic existing between memory, obliviousness and corporality. She contends that recent films, produced during and after the Second Intifada and situated in the city, juxtapose the traditional imagery of the city with its bleak daily life. Drawing spaces and routes through their body they suggest fragmented narratives, between the personal and the collective memory of the city, as an alternative to the hegemonic narrative and time linearity. Zanger analyzes three films, each in its own way tracing the relationship between city-memory and subject: The Cemetery Club (Dir. Tali Shemesh, 2006); Jerusalem’s Cuts (Dir. Liran Atzmor, 2008); and Seven Minutes in Heaven (Dir. Omri Givon, 2008). In all of them, the past slips through the corporality of the present while practices of walking, strolling and forbidden driving allude to competing narratives of the past. Older women who survived the Holocaust, a young woman who survived a terror attack, as well as Jewish and Palestinian residents of Jerusalem and veterans of the 1948War - through their "speech-acts" all point to Jerusalem as a place that has lost the keys to its memory.